ZnO/Cu2O/g-C3N4 heterojunctions with enhanced photocatalytic activity for removal of hazardous antibiotics - Yujie Zhu; Ling Wang; Wentao Xu; Zehai Xu; Junsheng Yuan; Guoliang Zhang (Heliyon, 2022)
In view of the environmental pollution caused by antibiotics, the creation of an efficient photocatalytic material is an effectual way to carry out water remediation. Herein, we developed a smart strategy to synthesize ZnO/Cu2O/g-C3N4 heterojunction photocatalysts for the photodegradation of hazardous antibiotics by one-pot synthesis method. In this system, the Cu2O nanoparticles with electrons reducing capacity were coupled with g-C3N4 composites. The photocarriers were generated from the electric field of type Ⅰ heterojunction between ZnO and g-C3N4 and type Ⅱ heterojunction between Cu2O and g-C3N4. ZnO as a co-catalyst was doped to Cu2O/g-C3N4 catalyst system for removal of broad-spectrum antibiotics with the condition of visible light to protect Cu2O from photocorrosion, which thereby accelerated photocatalytic reactivity. Benefiting by new p-n-n heterojunction, the resulting ZnO/Cu2O/g-C3N4 composites had an excellent degradation performance of broad-spectrum antibiotics such as tetracycline (TC), chlortetracycline (CTC), oxytetracycline (OTC) and ciprofloxacin (CIP), the degradation of which were 98.79%, 99.5%, 95.35% and 73.53%. In particular, ZnO/Cu2O/g-C3N4 photocatalysts showed a very high degradation rate of 98.79% for TC in first 30 min under visible light, which was 1.35 and 10.62 times higher than that of Cu2O/g-C3N4 and g-C3N4, respectively. This work gives a fresh visual aspect for simultaneously solving the instability deficiencies of traditional photocatalysts and improving photocatalytic performance.